PENERAPAN MODEL COOPERATIVE SCRIPT PADA TEMA CITA-CITAKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS IV - Ammi Al-Habiby Telaumbanua (Universitas Negeri Medan, 2023)
Abstract: The purpose of this study is to improve student learning outcomes using the Cooperative Script model on the Theme of My Goals in Class IV SD Negeri 060870 T.A 2021/2022. This type of research is classroom action research which is carried out with 2 cycles and 4 stages: planning, implementation, observation, and reflection. The research subjects were the fourth grade students of SD Negeri 060870, totaling 24 people. Data collection tools used are learning outcomes tests and observation sheets. Based on the results of the research above, it can be concluded that the results of the initial test (pre test) of students still experience a learning mastery level below the average, which is 43.9 with a classical mastery percentage of 20.83%. After the first cycle, there was an increase in which 10 students scored 70 or incomplete (41.67%) and 14 students (58.33%). This shows that the value of student learning outcomes in the first cycle has not reached the level of learning success (classical completeness) because it is still below 85%. Based on the results of the research on the implementation of the second cycle, it can be seen that 22 people (91.67%) have completed, and 2 people (8.33%) have not. The classical completeness level reaches 92% which indicates that the classical learning outcomes have been completed (≥85%). In the first cycle the teacher's teaching activities were categorized as good with an average percentage of 66.66%, and in the second cycle the teacher's teaching activities increased with an average percentage of 90% with a very good category. In the first cycle, student learning activities were classified as poor with an average percentage of 62.50%, while in the second cycle, student learning activities increased with a percentage of 93.75% in good category.Keywords: Learning Outcomes, Cooperative Script.Abstrak: Tujuan dari penelitian ini adalah untuk meningkatkan hasil belajar siswa menggunakan model Cooperative Script pada Tema Cita-Citaku di Kelas IV SD Negeri 060870 T.A 2021/2022. Jenis penelitian ini adalah penelitian tindakan kelas (clasroom action research) yang dilaksanakan dengan 2 siklus dan 4 tahapan yaitu: perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SD Negeri 060870 yang berjumlah 24 orang. Alat pengumpulan data yang digunakan adalah tes hasil belajar dan lembar observasi. Berdasarkan hasil penelitian diatas, dapat disimpulkan bahwa hasil tes awal (pre test) siswa masih mengalami tingkat ketuntasan belajar dibawah rata-rata yaitu 43,9 dengan persentase ketuntasan klasikal 20,83%. Setelah dilakukan siklus I terjadi peningkatan dimana siswa yang memperoleh nilai ≤70 atau tidak tuntas sebanyak 10 orang (41,67%) dan yang memperoleh nilai ≥ 70% atau tuntas sebanyak 14 orang (58,33%). Hal ini menunjukkan bahwa nilai hasil belajar siswa pada siklus I belum mencapai tingkat keberhasilan belajar (ketuntasan klasikal) karena masih dibawah 85%. Berdasarkan hasil penelitian pelaksanaan siklus II dapat diketahui bahwa 22 orang (91,67%) tuntas, dan 2 orang (8,33%) yang belum tuntas. Tingkat ketuntasan klasikal mencapai 92% yang menunjukkan bahwa hasil belajar klasikal telah tuntas (≥85%). Pada siklus I aktivitas mengajar guru tergolong kategori baik dengan persentase rata-rata yaitu 66,66%, dan pada siklus II aktivitas mengajar guru mengalami peningkatan dengan persentase rata-rata yaitu 90% dengan kategori sangat baik. Pada siklus I aktivitas belajar siswa tergolong dalam kategori kurang dengan persentase rata-rata pada yaitu 62,50% sedangkan pada siklus II aktivitas belajar siswa mengalami peningkatan dengan persentase yaitu 93,75% dengan kategori baik. Kata kunci: Hasil Belajar, Cooperative Script